Matched-pair analysis of a multi-institutional cohort reveals that epidermal growth factor receptor mutation is not a risk factor for postoperative recurrence of lung adenocarcinoma. (December 2017) - Matsumura, Yuki; Suzuki, Hiroyuki; Ohira, Tetsuya; Shiono, Satoshi; Abe, Jiro; Sagawa, Motoyasu; Sakurada, Akira; Katahira, Masato; Machida, Yuichiro; Takahashi, Satomi; Okada, Yoshinori
Highlights: EGFR mutation status influences the survival of lung adenocarcinoma (ADC). It is uncertain if this mutation effects on postoperative recurrence of ADC. Patients' backgrounds are different between EGFR-mutated and wild-type ADCs. We matched their backgrounds and compared the survivals of the matched cohort. Both recurrence-free and overall survivals were not significantly different. Abstract: Objective: It is unclear whether epidermal growth factor receptor (EGFR) mutation status is a risk factor for postoperative recurrence of surgically resected lung adenocarcinoma (ADC). Therefore, we conducted a multi-institutional study employing matched-pair analysis to compare recurrence-free survival (RFS) and overall survival (OS) of patients with lung ADC according to EGFR mutation status. Methods: We collected the records of 909 patients who underwent surgical resection for lung ADC between 2005 and 2012 at five participating institutions and were also examined their EGFR mutation status. For each patient with an EGFR mutation, we selected one with the wild-type EGFR sequence and matched them according to institution, age, gender, smoking history, pathological stage (pStage), and adjuvant treatment. We compared RFS and OS of the matched cohort. Results: The patients were allocated into groups (n = 181 each) with mutated or wild-type EGFR sequences. Both cohorts had identical characteristics as follows: institution, median age (68 years), men (85, 47%), ever smokers (77, 43%), and pStage (IA, 108, 60%; IB, 48, 27%; II, 14, 8%; III, 11, 6%). The 3- and 5-year RFS rates of patients with mutated or wild-type EGFR sequence were 79%, 68% and 77%, 68%, respectively ( p  = 0.557). The respective OS rates were 92%, 81%, and 89%, 79% ( p  = 0.574). Conclusion: Matched-pair and multi-institutional analysis reveals that an EGFR mutation was not a significant risk factor for recurrence of patients with surgically resected lung adenocarcinoma.